A lightweight micropayment scheme based on Lagrange interpolation formula. Issue 8 (30th October 2012) - Liu, Yining; Yan, Jihong
ABSTRACT On the basis of hash chain and Lagrange interpolation formula over a finite field, a lightweight micropayment scheme is proposed. Compared with Micali and Rivest's micropayment scheme, the improved scheme achieves three additional properties to ensure it suitable for mobile network. First it reduces the computing burden without digital signature algorithm, which is essential for limited mobile terminal. Second, the user, the merchant, and the bank are all equally involved in the selection of payable checks, which ensure the proposed scheme is fair for all parties. Moreover, the privacy of scheme is also achieved for the computational infeasibility of calculating the inverse of secure one‐way function. The improved micropayment scheme is secure, fair, and efficient, and privacy‐preserving, especially suitable for mobile network. Copyright © 2012 John Wiley & Sons, Ltd.